Scoping Review: Strategi Efisiensi Biaya Rumah Sakit pada Tindakan Operatif di Berbagai Negara - Anastasia Piramitha Angela Soesanto; Ayun Sriatmi; Septo Pawelas Arso (Jurnal Ragam Pengabdian, 2026)
The healthcare sector faces global challenges in controlling service costs, particularly in operative procedures that require substantial resources, including highly skilled medical personnel, advanced medical technology, and adequate supporting facilities. These circumstances encourages hospitals to implement various strategies to improve cost efficiency while maintaining the quality of care. This study aims to review cost-efficiency strategies implemented by hospitals in managing operative procedures across different countries. A scoping review was conducted using the PRISMA approach. Literature searches were conducted in the PubMed, Scopus, Google Scholar, Web of Science, and Cochrane Library databases for articles published between January 2020 and May 2025. A total of 14 articles were analyzed. Effective strategies include the implementation of standardized clinical protocols such as Enhanced Recovery After Surgery (ERAS) and fast-track surgery, optimization of medical technologies, unit cost analysis, application of lean management principles, and more flexible human resource management. Cost-efficiency strategies in operative care vary considerably, and no single universal approach can be applied across all healthcare settings. The effectiveness of these strategies depends on the specific context of each hospital, including the availability of resources, the types of surgical procedures performed, and the characteristics of the healthcare system.